Improvement using frequency relays compared to dynamic and static relays in frequency instability - Rasaei, A; Emamhosseini, A (Bangladesh Journal of Scientific and Industrial Research, 2017)
Nowadays a smarter, more diverse and robust electricity infrastructure is necessary because power grids form one of the most effective components of the infrastructure on which modern society depends on. The stability of an electrical grid is very important for suppliers and consumers. Frequency variations cause instability in the electricity grid. There will be so many problems such as overproduction, overloading, and etc. which have irreversible effects on suppliers and consumers. Balancing the isolated systems in terms of production and consumption, and also using the frequency relays in power grids are useful ways to solve these problems. Due to the importance of frequency relays in proportion than dynamic and static relays, designing and optimizing the frequency relays are very important to guarantee the stability of the electrical grid. The frequency relays can be used in a different network with different charges. The frequency relays have two parts, namely measurement, and detection which undertake separate tasks. In this paper, we investigated the function of frequency relays. We also simulated and analyzed the aforementioned issues. The simulation provides a comparison of grid charge variations and nominal frequency in a state of disarray and approach to the ideal state. Some blocks have been used for counting the frequency in this simulation which most notably, included a block of frequency measurement and another block that has the protection duty. Bangladesh J. Sci. Ind. Res. 52(4), 289-294, 2017